Polymerization of Vinyl Monomers by Mn(III)-L-methionine Redox System - A Kinetic Study - Kavitha, S.; Subbu, S. (Asian Journal of Chemistry, 2010)
The polymerization of methyl acrylate and methacrylic acid initiated by Mn(III)-L-methionine redox system in aqueous sulphuric acid medium has been investigated. The effects of variation of [monomer], [Mn(III) ion], [L-methionine], [H+] and ionic strength on the rates of polymerization and Mn3+ ion disappearance have also been studied. The effect of temperature on the polymerization rate was studied and the thermodynamic parameters were determined. An appropriate mechanism consistent with the kinetic observations has been suggested. A comparative study of the reactivities of two vinyl monomers has been made on the basis of the rate coefficients of the monomers.